Artificial micro RNA (amiRNA)-mediated resistance against whitefly (Bemisia tabaci) targeting three genes. (November 2020) - Zubair, Muhammad; Khan, Muhammad Zuhaib; Rauf, Imran; Raza, Amir; Shah, Azhar Hussain; Hassan, Ishtiaq; Amin, Imran; Mansoor, Shahid
Abstract: Whitefly ( Bemicia tabaci ) is an insect pest that causes severe losses in economically important crops by sucking the plant sap and transmitting plant viruses. We used the promising new approach of plant-mediated artificial miRNA (amiRNA) expression against three essential genes of whitefly. The Arabidopsis thaliana miR159 precursor was modified and engineered to express artificial miRNAs (amiRNAs) targeting three vital genes of whitefly, sex lethal (Sxl) protein, acetylcholinesterase ( AChE ) and orcokinin ( Orc ). The amiRNA WF construct was transformed into the Nicotiana tabacum plants. Whiteflies were infested in separate cages on both control and transgenic plants. After four weeks of infestation, the nymphs were counted and real time quantitative PCR (RT-qPCR) was performed to assess the relative expression of whitefly genes. The transgenic N . tabacum plants showed resistance against whitefly and the number of whiteflies in the next generation were substantially reduced on transgenic plants compared to control plants. Abnormal egg hatching and poor development was observed and only a small number of whitefly nymphs matured to adults. RT-qPCR results indicated that the expression of target genes (Sxl, AChE and Orc ) in the nymphs was considerably down-regulated in whiteflies reared on transgenic plants. The amiRNA mediated resistance against whitefly in transgenic plants may pave the way for engineering resistance against whitefly in cotton plants.